haskellmonadscategory-theorymonoids

How are Haskell Monad laws derived from Monoid laws?


The laws for monoids in the category of endofunctors are:

monoid laws

And the Haskell monad laws are:

Left identity: return a >>= k = k a

Right identity: m >>= return = m

Associativity: m >>= (\x -> k x >>= h) = (m >>= k) >>= h

I'm assuming the latter is derived from the former, but how so? The diagrams basically say

join (join x) = join (fmap join x)
join (return x) = x
join (fmap return x) = x

How are these equivalent to the Haskell monad laws?


Solution

  • To show the >>=-monad laws from the join-monad laws, one needs to define x >>= y in terms of multiplication (join), unity (return), and functoriality (fmap), so we need to let, by definition,

    (x >>= y) = join (fmap y x)
    

    Left identity law

    The left identity law then becomes

    return a >>= k = k a
    

    By definition of >>=, it is equivalent to

    join (fmap k (return a)) = k a
    

    Now, return is a natural transformation I -> T (where I is the identity functor), so fmap_T k . return = return . fmap_I k = return . k. We reduce the law to:

    join (return (k a)) = k a
    

    And this follows by the join laws.

    Right identity law

    The right identity law

    m >>= return = m
    

    reduces to, by definition of >>=:

    join (fmap return m) = m
    

    which is exactly one of the join laws.

    I'll leave the associativity law for you to prove. It should follow using the same tools (join laws, naturality, functoriality).